The Relationship Between Procurement Skills and Procurement Performance in the Kumasi Metropolis of Ghana - Johnson Nsowah; Francis Adomako; Evelyn Nsiah Asare; Samuel Kusi; Augustine Anane (International Journal of Environmental, Sustainability, and Social Science (IJESSS), 2026)
The dynamic nature of the business environment has a significant influence on Purchasing and Supply Chain Management (PSCM), resulting in a transformation of its role from being mostly administrative to being more strategic in nature. The study was carried out to assess the relationship between procurement skills and procurement performance in the Kumasi Metropolis of Ghana. The study utilized the quantitative research approach. The research used a stratified sampling approach to randomly choose the manufacturing industries. The analysis was performed with the aid of the statistical software namely, Statistical Package for Social Sciences (SPSS) version 23. The result shows that, the respondents somewhat agreed on the following statement, company has the ability to manage risks involved in procurement undertakings (M=5, SD=1), their company has the global skills to follow procurement (M=5, SD=1), their company has the ability to analyze second-tier suppliers (M=5, SD=1), their company has the ability to effectively manage their own time (M=5, SD=1). The study found that, procurement skills had significant effect on procurement performance. The study concludes that, procurement skills is significant predictor of procurement performance, that is when firms effectively implement it in their procurement systems it will enhance performance of the company. The study recommends that, there is a need for the company to improve their value chain in order to increase the frequency usage of information needed. Also, the managers and the heads of the various departments and units should to create time, resources in training of employees in using new system.